Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1037/a0038659
|View full text |Cite
|
Sign up to set email alerts
|

Job insecurity and organizational citizenship behavior: Exploring curvilinear and moderated relationships.

Abstract: This article examined a curvilinear relationship between job insecurity and organizational citizenship behavior (OCB). Drawing from social exchange theory and research on personal control, we developed and tested an explanation for employees' reactions to job insecurity based on their conceptualization of their social exchange relationship with the organization at different levels of job insecurity. Using data from 244 Chinese employees and 102 supervisory ratings of OCB, we found support for a U-shaped relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(196 citation statements)
references
References 98 publications
7
170
0
2
Order By: Relevance
“…Furthermore, as recommended by Bagozzi and Edwards () (see also Lam et al. 's () empirical study), we formed five parcels of items as indicators for proactive personality by averaging the items with the highest and lowest loading. The results of CFAs in Table showed that the six‐factor base model fit data best among all models we examined, χ 2 = 768.99, df = 260, χ 2 /df = 2.96, RMSEA = 0.07, Tucker‐Lewis index (TLI) = 0.90, comparative fit index (CFI) = 0.91.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as recommended by Bagozzi and Edwards () (see also Lam et al. 's () empirical study), we formed five parcels of items as indicators for proactive personality by averaging the items with the highest and lowest loading. The results of CFAs in Table showed that the six‐factor base model fit data best among all models we examined, χ 2 = 768.99, df = 260, χ 2 /df = 2.96, RMSEA = 0.07, Tucker‐Lewis index (TLI) = 0.90, comparative fit index (CFI) = 0.91.…”
Section: Resultsmentioning
confidence: 99%
“…Expatriates may then achieve retention or perform better during their assignment. This outcome can be achieved by building an informal communications network within the organization to expedite information sharing (Lam et al, 2015) or by periodically hosting informal gatherings to ensure that employees feel valued even when off duty (Ngo, Foley, & Loi, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, findings on the relationship between job insecurity and job performance can be described as 'mixed'with studies either finding no (e.g., Sverke et al, 2002) or a slightly negative relationship (e.g., Cheng and Chan, 2008). To explain these findings, researchers have argued that the job insecurity-job performance relationship might be more complex than a simple linear relationship (e.g., Selenko et al, 2013;Staufenbiel and König, 2010), thereby also recommending the use of longitudinal research designs (see also Huang et al, 2013;Lam et al, 2015). In the present conceptual paper, we further this proposition by arguing that the duration of job insecurity and the appraisal of job insecurity are crucial for gaining a more holistic understanding in terms of job insecurity's effects on job performance.…”
Section: Job Insecurity Duration and Job Performancementioning
confidence: 99%